The reawakening of teaching through aesthetics in education: Students’ perspectives - Jugathambal Ramdhani; Sarita Ramsaroop (Koers : Bulletin for Christian Scholarship, 2015)
Abstract A multidisciplinary approach to teacher education involves drawing from multiple pedagogies within disciplines, in particular the use of aesthetic methods of teaching, to redefine teaching through continuous reflection. This article reports on the process of pre-service students’ interpretation of the sensory contemplation of aesthetic perceptiveness within their academic programmes at a higher education institution and explores how students internalised and applied these aesthetic qualities in their practice. Using a qualitative approach, the findings indicate the positive influence of aesthetically enjoyable and engaging teaching strategies, such as group or whole class discussions that infused technology, on pre-service students’ understanding of content knowledge taught in lectures. Reports regarding pre-service students’ application of these very strategies at schools during their school experience were positive in terms of their ability to reflect critically before, during and after the lesson, made possible by personal first-hand experiences with the selected strategy. It was found that pre-service teachers believe that for effective teaching to take place, as practitioners, they need to take ‘full account of the multi-dimensional cultural world of the learner’ and therefore it is recommended that they adopt a multi-dimensional approach that is inclusive of aesthetics in their practice. Keywords: Aesthetics; teacher education; prior learning; constructivism, pedagogy, higher education; student teacher learning